Intercalation Study of Low‐Molecular‐Weight Hyperbranched Polyethyleneimine into Graphite Oxide. Issue 26 (7th May 2014) - Tsoufis, Theodoros; Katsaros, Fotios; Sideratou, Zili; Kooi, Bart J.; Karakassides, Michael. A.; Siozios, Anastasios
Abstract We report for the first time the intercalation of low‐molecular‐weight hyperbranched polyethyleneimine (PEI) into graphite oxide (GO) for the facile, bulk synthesis of novel graphene‐based hybrid (GO‐PEI) materials exhibiting tailored interlayer galleries. The size of the intercalant as well as the loading in GO were systematically investigated to determine their contribution to the basal spacing of the resulting materials. Powder X‐ray diffraction measurements demonstrated the generation of constrained hybrid systems along the c axis that exhibit considerably increased interlayer distances compared with the starting, pristine GO. The results of X‐ray photoelectron and FTIR studies are consistent with a "grafting‐to" process of the intercalated PEI with the oxygen functional groups present along the GO framework. Furthermore, it was found that a great number of the nitrogen‐containing groups in PEI still remain available within the newly formed, confined micro‐environment of intercalated GO galleries. The increased surface area of the GO‐PEI hybrids in conjunction with the remaining available active groups of intercalated PEI render the synthesised hybrids very attractive candidates as nanostructured adsorbents.